Ordered B-site vacancies in an ABX3 formate perovskite - Boström, HJB; Bruckmoser, J; Goodwin, AL (American Chemical Society, 2019)
We report the synthesis and structural characterization of the ABX3 perovskite frameworks [C(NH2)3]Mn1–x2+(Fe2x/33+,□x/3)(HCOO)3 (□ = B-site vacancy). For large x, the vacancies order, lowering the crystal symmetry. This system establishes B-site vacancies as a new type of defect in formate perovskites, with important chemical, structural, and functional implications. Monte Carlo simulations driven by nearest-neighbor vacancy repulsions show checkerboard vacancy order to emerge for x > 0.6, in accord with experiment.